2012
DOI: 10.1111/j.1745-3933.2012.01293.x
|View full text |Cite
|
Sign up to set email alerts
|

A peculiar galaxy appears at redshift 11: properties of a moderate-redshift interloper

Abstract: In 2011 Laporte et al. reported a very high redshift galaxy candidate: a lensed J-band dropout (A2667-J1). J1 has a photometric redshift of z = 9.6-12, the probability density function for which permits no low-or intermediate-z solution. We here report new spectroscopic observations of this galaxy with Very Large Telescope/X-Shooter, which show clear [O III] λ5007Å, Lyα, Hα and Hβ emission and place the galaxy firmly at z = 2.082. The oxygen lines contribute only ∼25 per cent to the H-band flux and do not sign… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 33 publications
1
37
0
Order By: Relevance
“…Indeed, recent spectroscopic studies have shown that most of the interlopers that contaminated z ∼ 8 samples are at z ∼ 2 (e.g., Pénin et al 2014;Brammer et al 2013;Hayes et al 2012). For all objects, the best-fit SED has a significantly larger χ 2 and for three of them requires higher dust reddening than in the previous case.…”
Section: Sed-fittingmentioning
confidence: 95%
See 1 more Smart Citation
“…Indeed, recent spectroscopic studies have shown that most of the interlopers that contaminated z ∼ 8 samples are at z ∼ 2 (e.g., Pénin et al 2014;Brammer et al 2013;Hayes et al 2012). For all objects, the best-fit SED has a significantly larger χ 2 and for three of them requires higher dust reddening than in the previous case.…”
Section: Sed-fittingmentioning
confidence: 95%
“…Thanks to A&A 575, A92 (2015) the ever-increasing numbers of objects, the evolution and properties of galaxies is relatively well constrained up to z ∼ 6, with many secure spectroscopic confirmations (e.g., Jiang et al 2013;Willott et al 2013;Stark et al 2014;Curtis-Lake et al 2013;Schenker et al 2012;Le Fevre et al 2015). Beyond z ∼ 6, however, spectroscopic follow-up remains extremely challenging as a result of the decreasing mean brightness of these objects (Finkelstein et al 2013) and the nature of extreme mid-z interlopers that may contaminate the high-z sample (Hayes et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The remaining galaxies that can enter the selection need to have a large Balmer break and relatively blue continuum at longer wavelengths. The existence of these peculiar objects has been discussed in Hayes et al (2012), where aspectral energy distribution (SED) of a young burst superimposed on an old stellar population with an extreme 4000 Å break can mimic the Lyman break colors. Such objects should be very rare and represent only a minor contamination.…”
Section: Sources Of Contaminationmentioning
confidence: 99%
“…This object is characterized by a high EW and it has [OIII]5007/Hβ ∼ 5.9 fully consistent with USEL values. Similarly, Hayes et al (2012) followed a z ∼ 11 LBG candidate with X-Shooter and detected several emission lines, amongst which [OIII] is the strongest with an EW of ∼700 Å, which put that galaxy at z = 2.08. They conjecture that this object is either a heavily obscured starburst or an old galaxy upon which a burst of star formation is superimposed.…”
Section: Discussion and Implication For High-z Surveysmentioning
confidence: 99%
“…It is expected that contamination increases with redshift, when the objects are fainter and less constrained from their photometry since the object may be detected in one or two bands only. This is exemplified by the spectroscopic identification at a redshift of 2.08 of an LBG candidate at z ∼ 11 (Hayes et al 2012) and the likely identification at a redshift of 2.19 of another LBG candidate at z ∼ 12 (Brammer et al 2013;Capak et al 2013). In an independent parallel survey with HST/WFC3, Atek et al (2011) show that extreme emission line galaxies at z ∼ 1−2 can mimic the broadband colours of z ∼ 8 LBGs, the high equivalent width (EW) lines being mistaken for the break at the Lyα line.…”
Section: Introductionmentioning
confidence: 99%